Historie alternatywne − pomiędzy pisarstwem historycznym a fantastycznym, czyli czasem tertium est datur… - Lemann, Natalia (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The aim of this article is to define alternative history genre (branch of fantastic literature) as a participating in the historical writing formula (H. White). The author juxtaposes literary studies, literature and history as neighboring branches of humanistic knowledge. Alternate history genre could be displaced as displaced by both, the history and literary studies. This genre, as a type of fantastic literature, is understood as dangerous phantasm, because of fictional abilities. In this article historiography and literary studies are diagnosed as forming a sisterhood relationship. When the opportunity arises, it is shown that the idea of postmodern history is no novelty, since until the decline of the 18th century history did not stand in oppossition to literature. Actually, the way of thinking about history as an (literary) art has a splendid tradition rooted in antiquity. It is shown that, in fact, there is no essential difference between alternate history (as a branch of fantastic literature) and counterfactualism as a methodology of history. It drives the author to a conclusion − by comparison of the methodologies of history and literary studies in the field of narrativity, and, according to Hayden White, comprehends history as a type of fiction, historio-graphia, literary artifact, or historical writing – that the alternative history novel could be understood as a third path to reconcile literary studies and historical studies. The participation of popular culture, where the alternate history genre and fantastic literature traditionally belongs, makes the history and literary studies more transgressive, widely open for the contemporary forms of communication and more hearable.